Correction to Mneimneh (2019): "Simple variations on the Tower of Hanoi: A study of recurrences and proofs by induction” Teaching Mathematics and Computer Science 17 (2019), 131-158. - Mneimneh, Saad (Teaching Mathematics and Computer Science, 2023)
In the article “Simple variations on the Tower of Hanoi: A study of recurrences and proofs by induction” by Saad Mneimneh (Teaching Mathematics and Computer Science, 2019, 17(2), 131–158. https://doi.org/10.5485/TMCS.2019.0459), there was an error in Table 1 (p. 155), and consequently, the first paragraph of Section 8 (p. 154) also needed correction.